Interval estimation for the area under the receiver operating characteristic curve when data are subject to error - Li, Yanhong; Koval, John J.; Donner, Allan; Zou, G. Y. (Statistics in medicine, 2010)
The area (A) under the receiver operating characteristic curve is commonly used to quantify the ability of a biomarker to correctly classify individuals into two populations. However, many markers are subject to measurement error, which must be accounted for to prevent understating their effectiveness. In this paper, we develop a new confidence interval procedure for A which is adjusted for measurement error using either external or internal replicated measurements. Based on the observation that A is a function of normal means and variances, we develop the procedure by recovering variance estimates needed from confidence limits for normal means and variances. Simulation results show that the procedure performs better than the previous ones based on the delta‐method in terms of coverage percentage, balance of tail errors and interval width. Two examples are presented. Copyright © 2010 John Wiley & Sons, Ltd.